Implementasi Plex Media Server dan Adguard Home pada Raspberry pi sebagai Home Server - Hermawan, Rudi; Maesaroh, Siti; Adhy, Dewanto Rosian; Juharsa, Jujun; Patriana, Ari (INNOVATICS: International Journal on Innovation in Research of Informatics, 2021)
The computer revolution to this day continues to occur, current progress makes many variations of computer technology, especially those used for servers, Raspberry pi is a mini computer designed for minimalist servers. On the other hand, the high and fast flow of technology raises new problems, one of which is the issue of data security through threats embedded in advertisements and age-appropriate content filtering. This research was conducted using a Raspberry pi with Plex media server service and configuring a DNS Server to filter content with the Adguard Home application as Family protection. With the developments and problems above, it can be taken from the reliability of the Raspberry pi as a home server that was built and became a solution, with the service features of the plex media server and adguard home. Both server services can be used as a home server and family protection to maintain the security of data inserted through advertisements and content filtering, especially content in the form of video or sound.